2020
DOI: 10.1111/pde.14418
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous reactions to pediatric cancer treatment: Part I. Conventional chemotherapy

Abstract: Cutaneous side effects of childhood cancer therapies contribute to patient morbidity and can negatively affect quality of life. Traditional cancer therapies target rapidly dividing tissues; thus, many of their side effects inevitably involve the skin, nails, and mucosal surfaces. It is important for clinicians to recognize cutaneous reaction patterns and understand the underlying mechanisms of chemotherapeutic agents to detect and manage symptoms early and allow for continuation of therapy. In this scoping rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 82 publications
(99 reference statements)
0
1
0
3
Order By: Relevance
“…Al momento de presentar la lesión dermatológica estaban en tratamiento oncológico el 62.8% (54/86). Según la localización de la lesión fue piel 47.6% (41/86); de esta más frecuente dermatitis 19 El manejo de las lesiones dermatológicas fue con miconazol 37.2% (32/86). Se reportó el fallecimiento de 4.7% (4/86) pacientes siendo la causa base de muerte la hemorragia intraventricular, meduloblastoma, osteosarcoma y linfoma No Hodgkin respectivamente.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Al momento de presentar la lesión dermatológica estaban en tratamiento oncológico el 62.8% (54/86). Según la localización de la lesión fue piel 47.6% (41/86); de esta más frecuente dermatitis 19 El manejo de las lesiones dermatológicas fue con miconazol 37.2% (32/86). Se reportó el fallecimiento de 4.7% (4/86) pacientes siendo la causa base de muerte la hemorragia intraventricular, meduloblastoma, osteosarcoma y linfoma No Hodgkin respectivamente.…”
Section: Resultsunclassified
“…antibióticos tumorales en poco más de la mitad de los casos. Esto está de acuerdo con lo referido en la literatura por Sous D, et al, respecto a que los inhibidores mitóticos que derivan de compuestos alcaloides de plantas están indicados para tumores sólidos recidivantes o refractarios en pediatría y se han asociado a reacciones como erupción cutánea, mucositis, alopecia, edema y con algunas formas de dermatitis que se desarrollan desde unos pocos días desde el inicio del tratamiento, hasta dos semanas después de la administración del fármaco, 19 así también, nuestros hallazgos son similares a los descrito por Shi V, et al; respecto a que la mucositis está asociada a terapia citotóxica hasta en 40% de los casos. 20 que en nuestro estudio fue del 36% (31/86).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Chemotherapy, as the literature shows ( Sous et al, 2021 ), causes painful side effects on the skin, nails, and mucosa by quickly dividing tissue. A cross-sectional study revealed that 73.4 percent of pediatric patients reported dry mouth and 61.8 percent a change in taste as side effects of chemotherapy ( García-Chías et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%